Perlindungan Hukum Terhadap Hak Pekerja Perempuan di Indonesia Berdasarkan Teori Konflik Sosial Max Weber : Penelitian - Putri Syakbania Dalimunthe; Agusmidah, Agusmidah; Harianto, Dedi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze legal protection for the rights of female workers in Indonesia through the perspective of Max Weber's Social Conflict Theory, which emphasizes the dimensions of class, status, and power. Normatively, various laws and regulations have provided a basis for protection, but their implementation still faces structural obstacles. This normative-sociological juridical research uses a conceptual and legislative approach with qualitative analysis of secondary data in the form of regulations and case studies. The results show that employment relations are still dominated by power imbalances between capital owners and female workers, which are reinforced by a patriarchal culture. In the class dimension, employers often avoid compliance costs, making female workers vulnerable to economic exploitation. In the status dimension, patriarchal norms weaken legal protection against discrimination, harassment, and maternity rights. Violations of maternity rights, wage and promotion discrimination, and high levels of sexual harassment reflect social conflicts resulting from economic domination and status, so that formal legal protection has not been substantively realized. This study concludes that the weak protection of female workers is not only due to legal implementation, but also to structural power imbalances.